Tax avoidance, tax evasion, and tax flight: Do legal differences matter? - Friedrich Schneider; Erich Kirchler; Boris Maciejovsky (Johannes Kepler University of Linz, Department of Economics, 2001)
Although from an economic point of view, legal considerations apart, tax avoidance, tax evasion and tax flight have similar effects, namely a reduction of revenue yields, and are based on the same desire to reduce the tax burden, it is likely that individuals perceive them as different and as unequally fair. Overall, 252 fiscal officers, business students, business lawyers, and entrepreneurs produced spontaneous associations to a scenario either describing tax avoidance, tax evasion, or tax flight, and evaluated it as positive, neutral or negative. The results indicate that social representations differ with respect to tax avoidance, tax evasion, and tax flight. Tax evasion was perceived rather negatively, tax flight neutrally, and tax avoidance positively. Tax knowledge was found not to be correlated neither with tax avoidance nor with tax evasion.
Keywords: H26; K34; K42; 330; tax evasion; social representations; tax knowledge; Steuervermeidung; Steuerkriminalität; Steuerflucht; Steuermoral; Sozialethik; Theorie